Stray bullets (1995), volume 3 ebook Other people. - Lapham, David (Stray Bullets (1995), 2015)
Beth and Virginia have relocated to Los Angeles where things only appear more normal... Take a ringside seat for these brutal tales of twisted emotion that will knock you to the mat and have you seeing stars... Collects STRAY BULLETS #15-22.. Author: David Lapham. Illustrator: David Lapham . 2015 David Lapham.